The Travelers Insurance Companies Pavilion, New York World's Fair, 1964-1965, "The Triumph of Man" (Dexter Press, Inc.)
This unique building is designed to resemble the Travelers famed symbol of insurance protection - the red umbrella. Within this unusual structure is the dramatic diorama "The Triumph of Man" showing man's struggle, growth and major achievements over the centuries.